![f(x)=(-8x+13)/(2x+9)](https://img.qammunity.org/2023/formulas/mathematics/college/i3xrdmp7sipo6bxr9qxdxe6sxuflidvqtn.png)
Vertical asymptote at x=a if the denominator is zero at x=a and the numerator isn't zero at x=a
Equal the denominator to zero and solve x:
![\begin{gathered} 2x+9=0 \\ 2x=-9 \\ x=-(9)/(2) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jway4177x4brotpe1v4a5jfxgj4zfnks5n.png)
Prove if x=-9/2 makes the numerator equal to 0:
![-8(-(9)/(2))+13=-(72)/(2)+13=-23](https://img.qammunity.org/2023/formulas/mathematics/college/90g81c8w5km1nzwuznn0pd13nrzko0ct51.png)
As the value x=-9/2 doesn't make the numerator be equal to zero the function has a vertical asymptote in x=-9/2
_______________
![f(x)=\frac{ax^n+\text{.}\ldots}{bx^m+\cdots}](https://img.qammunity.org/2023/formulas/mathematics/college/7y5oyf3n11c3327mbwqg375yrq8uzlmgik.png)
Numerator and denominator have the same largest exponent. Then, the line y=a/b is the horizontal asymptote:
![\begin{gathered} x=(-8)/(2) \\ \\ x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4g4w46g4752k54fo7v4sy591gbvjjnel0c.png)
Then, the given function has the next asymptotes:
Vertical asymptote: y= -9/2 (in red)
Horizontal asymptote: x= -4 (in blue)